Neurorehabilitation with vagus nerve stimulation: a systematic review - Korupolu, Radha; Miller, Alyssa; Park, Andrew; Yozbatiran, Nuray (Frontiers in Neurology, 2024)
Objective To systematically review vagus nerve stimulation (VNS) studies to present data on the safety and efficacy on motor recovery following stroke, traumatic brain injury (TBI), and spinal cord injury (SCI). Methods Data sources: PubMed, EMBASE, SCOPUS, and Cochrane. Study selection Clinical trials of VNS in animal models and humans with TBI and SCI were included to evaluate the effects of pairing VNS with rehabilitation therapy on motor recovery. Data extraction Two reviewers independently assessed articles according to the evaluation criteria and extracted relevant data electronically. Data synthesis Twenty-nine studies were included; 11 were animal models of stroke, TBI, and SCI, and eight involved humans with stroke. While there was heterogeneity in methods of delivering VNS with respect to rehabilitation therapy in animal studies and human non-invasive studies, a similar methodology was used in all human-invasive VNS studies. In animal studies, pairing VNS with rehabilitation therapy consistently improved motor outcomes compared to controls. Except for one study, all human invasive and non-invasive studies with controls demonstrated a trend toward improvement in motor outcomes compared to sham controls post-intervention. However, compared to non-invasive, invasive VNS, studies reported severe adverse events such as vocal cord palsy, dysphagia, surgical site infection, and hoarseness of voice, which were found to be related to surgery. Conclusion Our review suggests that VNS (non-invasive or invasive) paired with rehabilitation can improve motor outcomes after stroke in humans. Hence, VNS human studies are needed in people with TBI and SCI. There are risks related to device implantation to deliver invasive VNS compared to non-invasive VNS. Future human comparison studies are required to study and quantify the efficacy vs. risks of paired VNS delivered via different methods with rehabilitation, which would allow patients to make an informed decision. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=330653.